Does the Recovery of Respiratory Viruses Impact Pulmonary Function at Baseline and 1-, 6-, and 12-Month Follow-Up in People Living with HIV and Pneumonia? (2024)
ABSTRACT: The frequency of respiratory viruses in people living with HIV (PLHIV) and their impact on lung function remain unclear. We aimed to determine the frequency of respiratory viruses in bronchoalveolar lavage and induced sputum samples in PLHIV and correlate their presence with lung function. A prospective cohort of adults hospitalized in Medellín between September 2016 and December 2018 included three groups: group 1 = people diagnosed with HIV and a diagnosis of community-acquired pneumonia (CAP), group 2 = HIV, and group 3 = CAP. People were followed up with at months 1, 6, and 12. Clinical, microbiological, and spirometric data were collected. Respiratory viruses were detected by multiplex RT-PCR. Sixty-five patients were included. At least 1 respiratory virus was identified in 51.9%, 45.1%, and 57.1% of groups 1, 2 and 3, respectively. Among these, 89% of respiratory viruses were detected with another pathogen, mainly Mycobacterium tuberculosis (40.7%) and Pneumocystis jirovecii (22.2%). The most frequent respiratory virus was rhinovirus (24/65, 37%). On admission, 30.4% of group 1, 16.6% of group 2, and 50% of group 3 had airflow limitation, with alteration in forced expiratory volume at first second in both groups with pneumonia compared to HIV. Respiratory viruses are frequent in people diagnosed with HIV, generally coexisting with other pathogens. Pulmonary function on admission was affected in patients with pneumonia, improving significantly in the 1st, 6th, and 12th months after CAP onset.